Analisis Antropologi Sastra Dalam Novel Mangirurut Karya Bakhsan Parinduri Sebagai Alternatif Bahan Ajar di SMA - Luthfiah Zharifa; Dheni Harmaen; Lili Sadeli (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This study aims to describe (1) cultural elements in Bakhsan Parinduri’s Mangirurut novel; and (2) suitability of the analysis results as an alternative teaching material for high school students. The method used is descriptive qualitative. The approach use is the literary anthropology. The data source in this research is the novel Mangirurut by Bakhsan Parinduri. The results of the analysis show that (1) Bakhsan Parinduri’s Mangirurut novel contains cultural elements including: languange (bahasa bulung-bulung, surat tulak, and markusip); knowledge systems (how to work together, layout of dishes, how to eat, politeness, ways of survival, and education to children), kinship systems (dalihan na tolu, clan, and markobar); technology systems and living equipment (transportation, weapons, containers, and productive tools); livelihood systems (agriculture, hunting, plantations, and manyaraya); religious systems (religious activities); and the arts (musical instruments, gordang sambilan, margondang, and manortor); (2) utilization of the analysis results as an alternative learning material for students can be applied in learning novel texts for 11th grade in high school, namely in basic competency 3.7 with contextual learning methods.